X=(-4,0)
y=(0,9)
hope this helps
Answer:
x=1
Step-by-step explanation:
According to your typed question,
f(x)=2x-3
Let f(x)=y
y=2x-3
Now,
Interchanging the positions of x and y
x=2y-3
x+3=2y
x+3/2=y
f'(x)=x+3/2
Then,
f(x)=f'(x)
2x-3=x+3/2
2(2x-3)=x+3
4x-3=x+3
4x-x=3+3
3x=3
x=3/3
x=1
According to your image question,
f(x)=x/2x-3
f(x)=f'(x)
Now,
Let y=f(x)
y=x/2x-3
y(2x-3)=x
2xy-3=x
2xy-x=3
x(2y-1)=3
2y-1=3x
2y=3x+1
y=3x+1/2
f'(x)=3x+1/2
Then,
f(x)=f'(x)
x/2x-3=3x+1/2
2x=6xsq+2x-9x+3
2x=6xsq+7x+3
solve for x ok
Answer: 1 7/8
Step-by-step explanation:
Use 26/8 - 11/8 to get 15/8 then convert to mixed number
Answer:
y=-1/2x+3
Step-by-step explanation:
it has a negative slope and it's not that steep which is why the slope isnt 2. also the first one is wrong because the y-intercept is 3
Answer:
x^12.
Step-by-step explanation:
x^4 times x^4 times x^4.
Since we don't know x and the 4's are exponents we just add them together.